Desarrollo profesional hacia el dominio de la arquitectura de negocios - Vela Alfaro, Jorge Alejandro (2021)
As a professional graduated from the University of Lima, I have had to face a series of professional and personal challenges in different business areas, among which I can mention: Administrative Management, Research and Development, Operations Support, Project Management and Business Architecture , being able to apply my great university education, demonstrate my high professional level and use my extensive analytical capacity for the development and implementation of innovative technological solutions, obtaining great results by always being prepared to face the situation and the challenges that arose. The professional development that I detail in this document has allowed me to achieve the proficiency in the role of business architect by taking all the knowledge acquired, in the form of information and experience, aiming to ensure that the commercial strategy of the team I now belong aligns well with the technologies they offer.